2020
DOI: 10.9734/jamb/2020/v20i1130300
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility Effect of Bradyrhizobium japonicum and Trichoderma Strains on Growth, Nodulation and Physiological Traits of Soybean (Glycine max L.) under Water Deficit Conditions

Abstract: In the future, drought are expected to increase, affecting the productivity of crops sensitive to water scarcity. Through N2-fixation process, soybean is capable of achieving its nitrogen demands, however, this process is inhibited under drought stress conditions. Therefore, it is vital to find suitable solutions for the agricultural sustainability of soybean. Under pot experiment, biocompatibility was studied between Bradyrhizobium japonicum and Trichoderma strains (Trichoderma viride, T. harzianum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…On the basis of the recent literature [52][53][54], the hypothesis to verify is that this type of formulation could be useful in overcoming drought stress by improving plants' growth and final yield. The results obtained from the present experiment are compatible with what has already been reported in literature [54][55][56][57], and confirm the usefulness of the formulation in improving yields both in optimal water supply and in case of drought stress. In literature, it is reported that the factors influencing the efficacy of microbial treatments are complex and genotype dependent [27].…”
Section: Discussionsupporting
confidence: 92%
“…On the basis of the recent literature [52][53][54], the hypothesis to verify is that this type of formulation could be useful in overcoming drought stress by improving plants' growth and final yield. The results obtained from the present experiment are compatible with what has already been reported in literature [54][55][56][57], and confirm the usefulness of the formulation in improving yields both in optimal water supply and in case of drought stress. In literature, it is reported that the factors influencing the efficacy of microbial treatments are complex and genotype dependent [27].…”
Section: Discussionsupporting
confidence: 92%
“…Although, it was reported that some plant growth‐promoting rhizobacteria could have a positive effect on stress mitigation in dry environments (Niu et al, 2018) and also could play a vital role in reducing the adverse effects of drought, improving plant productivity (Khan et al, 2020), few reports mention Trichoderma effects on legume plants under stress plant conditions (Kaur & Kumar, 2020; Nahrawy et al, 2020). In this study, our results showed a positive response in soybean as in common bean after inoculation with two selected native T. harzianum , both under optimal irrigation or drought stress.…”
Section: Discussionmentioning
confidence: 92%
“…is a well-known cosmopolitan fungal organism usually used to enhance the growth of different plant species (Sharma et al, 2019), as a biocontroller of plant pathogens, and for providing tolerance to environmental stresses (Chepsergon et al, 2014). However, these effects depend on the potentiality and the specificity of Although, it was reported that some plant growth-promoting rhizobacteria could have a positive effect on stress mitigation in dry environments (Niu et al, 2018) and also could play a vital role in reducing the adverse effects of drought, improving plant productivity (Khan et al, 2020), few reports mention Trichoderma effects on legume plants under stress plant conditions (Kaur & Kumar, 2020;Nahrawy et al, 2020). In this study, our results showed a positive response in soybean as in common bean after inoculation with two selected native T. harzianum, both under optimal irrigation or drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Higher net photosynthetic rate, stomatal conductance, and RWC in soybean plants subjected to water stress and grown in saline soil were noticed due to increased CO 2 influx, transpiration rate, and photosystem II which, induced by combined application of PGPMs and K-humate, resulted in the production of plant growth hormones and IAA synthesis that increased water uptake together with increased nutrient uptake by vacuoles, collecting mainly in the cytosol [48].…”
Section: Discussionmentioning
confidence: 99%